2021
DOI: 10.3390/biomedicines9070770
|View full text |Cite
|
Sign up to set email alerts
|

Glycobiology of the Epithelial to Mesenchymal Transition

Abstract: Glycosylation consists in the covalent, enzyme mediated, attachment of sugar chains to proteins and lipids. A large proportion of membrane and secreted proteins are indeed glycoproteins, while glycolipids are fundamental component of cell membranes. The biosynthesis of sugar chains is mediated by glycosyltransferases, whose level of expression represents a major factor of regulation of the glycosylation process. In cancer, glycosylation undergoes profound changes, which often contribute to invasion and metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 136 publications
(153 reference statements)
1
11
0
Order By: Relevance
“…The results of this current study underline how NCR EMT can be identified, specifically and sensitively, by the surface expression shift from CD57 and other glycan moieties (CD15, CD24) towards a pro-migratory integrin panel of surface molecules including, most notably, CD51/61 (αVβ3). These results are corroborated by the alterations of glycan moities during epithelialto-mesenchymal transition and neural development [72][73][74][75]. Our data show that TWIST and SLUG as established intracellular NCR markers are most closely associated with a population uniquely characterized by shifting from CD57 to CD51/CD61 at the cell surface level.…”
supporting
confidence: 78%
“…The results of this current study underline how NCR EMT can be identified, specifically and sensitively, by the surface expression shift from CD57 and other glycan moieties (CD15, CD24) towards a pro-migratory integrin panel of surface molecules including, most notably, CD51/61 (αVβ3). These results are corroborated by the alterations of glycan moities during epithelialto-mesenchymal transition and neural development [72][73][74][75]. Our data show that TWIST and SLUG as established intracellular NCR markers are most closely associated with a population uniquely characterized by shifting from CD57 to CD51/CD61 at the cell surface level.…”
supporting
confidence: 78%
“…EMT has been shown to trigger some specific changes in glycosylation [ 33 , 55 , 56 ]. Therefore, it is possible that the initial glycophenotype of the SLC35A2 MDCK knockouts is further potentiated or additionally modified by EMT.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is commonly used to induce EMT in experimental conditions. Interestingly, glycosylation alterations are also associated with EMT [ 33 ]. It has to be emphasized that the nature of the link between glycosylation and EMT is bidirectional, as not only EMT drives specific changes in the cellular glycosylation patterns, but it can also be triggered by an altered glycosylation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the orchestration of multiple EMT-associated pathways and EMTassociated TFs by Forkhead box O (FOXO) proteins was also documented (Ma et al, 2018). The links with glycobiology (Pucci et al, 2021), Ca 2+ homeostasis (Jones and Hazlehurst, 2021) and the cytoskeleton (Leggett et al, 2021) were also explored, while the complexity of its interrelationships with CSCs (Roy et al, 2021), p53 (Parfenyev et al, 2021) or H 2 O 2 signaling (Milton and Konrad, 2022), and their consequences on the generation of circulating tumor cells (CTCs) (Topa et al, 2022) or occurrence of a collective invasion process (Nagai et al, 2020) were updated. Finally, as EMT is involved in such a broad range of processes associated with malignant transformation and invasiveness, it has become an increasingly interesting target for the development of new therapeutic strategies (Dudas et al, 2020;Jonckheere et al, 2022).…”
Section: Overview Of Emt Driving Parameters In Cancer An Updatementioning
confidence: 99%